Effectiveness Of Using Integrated Teaching Materials With Local Wisdom Character Values In Indonesian Language Subjects In Elementary School - Karim, Kodrat Hi; Srinawati, Risna; Abdullah, Taufik (Proceeding International Conference on Religion, Science and Education, 2025)
This study examines the effectiveness of the use of teaching materials integrated with the character values of local wisdom Ngale Se Cara and mangaji for the Indonesian Language subject on the Body Health Theme at the Elementary School 38 Ternate City. The main objective of the study was to see the effectiveness of teaching materials integrated with character values. The research model used ADDIE involving two parallel classes, namely the experimental class using integrated teaching materials and the control class with conventional methods. Data were collected through tests and character value instruments, classroom observations, and interviews with teachers and students. The results showed a significant increase in the experimental class in terms of learning outcomes, namely 80.43, while for the control class it was 56.02. While for the character values of students showed, the experimental class 86.27 and the control class 76.64. Qualitative analysis revealed that students who used teaching materials integrated with local wisdom showed an increase in awareness and appreciation of local wisdom and the application of its values in everyday life. These findings indicate that the integration of local wisdom character values into Indonesian language teaching materials is effective in improving learning outcomes and strengthening students’ character values.